Interplay between aggression, brain monoamines and fur color mutation in the American mink. (24th August 2016) - Kulikov, A. V.; Bazhenova, E. Y.; Kulikova, E. A.; Fursenko, D. V.; Trapezova, L. I.; Terenina, E. E.; Mormede, P.; Popova, N. K.; Trapezov, O. V.
Abstract : Domestication of wild animals alters the aggression towards humans, brain monoamines and coat pigmentation. Our aim is the interplay between aggression, brain monoamines and depigmentation. The Hedlund white mutation in the American mink is an extreme case of depigmentation observed in domesticated animals. The aggressive (−2.06 ± 0.03) and tame (+3.5 ± 0.1) populations of wild‐type dark brown color (standard) minks were bred during 17 successive generations for aggressive or tame reaction towards humans, respectively. The Hedlund mutation was transferred to the aggressive and tame backgrounds to generate aggressive (−1.2 ± 0.1) and tame (+3.0 ± 0.2) Hedlund minks. Four groups of 10 males with equal expression of aggressive (−2) or tame (+5) behavior, standard or with the Hedlund mutation, were selected to study biogenic amines in the brain. Decreased levels of noradrenaline in the hypothalamus, but increased concentrations of the serotonin metabolite, 5‐hydroxyindoleacetic acid and dopamine metabolite, homovanillic acid, in the striatum were measured in the tame compared with the aggressive standard minks. The Hedlund mutation increased noradrenaline level in the hypothalamus and substantia nigra, serotonin level in the substantia nigra and striatum and decreased dopamine concentration in the hypothalamus and striatum. Significant interaction effects were found between the Hedlund mutation and aggressive behavior on serotonin metabolism in the substantia nigra ( P < 0.001), dopamine level in the midbrain ( P < 0.01) and its metabolism in the striatum ( P < 0.05). These results provide the first experimental evidence of the interplay between aggression, brain monoamines and the Hedlund mutation in the American minks. Abstract : There is the interplay between aggression, brain monoamines and the Hedlund white color mutation in American minks. The Hedlund white color mutation increases brain serotonin level in the midbrain and substantia nigra in aggressive minks. Levels of serotonin (5‐HT) and 5‐hydroxyindoleacetic acid (5‐HIAA) as well as 5‐HIAA/5‐HT ratio in brain regions of standard (+/+) and Hedlund white (h/h) minks with tame or aggressive behavior towards man. * P < 0.05, ** P < 0.01, *** P < 0.001 vs. corresponding tame minks; # P < 0.05, ## P < 0.01, ### P < 0.001 vs. tame +/+ minks; @ P < 0.05, @@@ P < 0.001 vs. aggressive +/+ minks.